Transient stability of a hydro-turbine governing system with different tailrace tunnels. Issue 1 (2nd January 2020) - Zhang, Hao; Pang, Wentai; Chen, Diyi; Tian, Yu; Patelli, Edoardo; Li, Chaoshun; Zhou, Jianzhong
Abstract : This paper focuses on the transient stability of a hydro-turbine governing system with three kinds of tailrace tunnels. As the transfer coefficients change with operation conditions, the dynamic transfer coefficients which can describe the transient characteristics of the hydro-turbine governing system are introduced. Then, the transient stability of the hydro-turbine governing system is analysed. The global bifurcation diagrams for the three kinds of tailrace tunnels are respectively presented to investigate the effects of the tailrace tunnels on the stability of the hydro-turbine governing system. Theoretical analysis which proves the validity of simulation results is provided to explain the effects of the flow inertia and water level fluctuation. The influence of the tailrace tunnel gradient on the transient stability is also studied. More importantly, these methods and research results provide theoretical guidance for the arrangement of the tailrace tunnel and the operation of the hydropower station.